Update breast cancer 2019 part 1 - Implementation of study results of novel study designs in clinical practice in patients with early breast cancer = Update Mammakarzinom 2019 Teil 1 - Implementierung der Ergebnisse neuer Studienkonzepte beim frühen Mammakarzinom in die klinische Praxis - Hartkopf, Andreas; Schütz, Florian; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2019)
For many years, small but significant advancements have been made time and again in the prevention and treatment of early breast cancer. The so-called panel gene analyses are becoming more and more important in prevention, since the risk due to the tested genes is better understood and as a result, concepts for integration in health care can be developed. In the adjuvant situation, the first study in the so-called post-neoadjuvant situation was able to demonstrate a clear improvement in the prognosis with an absent pathological complete remission following trastuzumab or pertuzumab + trastuzumab. Additional studies with this post-neoadjuvant therapeutic concept are still being conducted at present. The CDK4/6 inhibitors which had shown a significant improvement in progression-free survival in a metastatic situation are currently being tested in the adjuvant situation in large therapeutic studies. These and other new data for the treatment or prevention of primary breast cancer are presented in this review against the backdrop of current studies.
Gesehen am 19.07.2019